2020
DOI: 10.1101/2020.04.21.20074021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between DNA Methylation Levels in Brain Tissue and Late-Life Depression in Community-Based Participants

Abstract: Objective: Major depressive disorder (MDD) arises from a combination of genetic and environmental risk factors and DNA methylation is one of the molecular mechanisms through which these factors can manifest. However, little is known about the epigenetic signature of MDD in brain tissue. This study aimed to investigate associations between brain tissue-based DNA methylation and late-life MDD. Methods: We performed a brain epigenome-wide association study (EWAS) of late-life MDD in 608 participants from the Reli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In depression, a discordant monozygotic twin study based on peripheral blood, found 39 DMRs associated to a lifetime history of MDD, which were significantly enriched in biological pathways associated to cytokine secretion (Zhu et al, 2020). Another EWAS on post-mortem brain of people with late-MDD (Hüls et al, 2020), found altered DNAm in the YOD1 locus, which is dysregulated in depression (Howren, Lamkin, & Suls, 2009) and its implicated in the regulation of inflammatory processes (Schimmack et al, 2017).…”
Section: Evidence Of Epigenetic Processes In Major Transdiagnostic Pa...mentioning
confidence: 99%
“…In depression, a discordant monozygotic twin study based on peripheral blood, found 39 DMRs associated to a lifetime history of MDD, which were significantly enriched in biological pathways associated to cytokine secretion (Zhu et al, 2020). Another EWAS on post-mortem brain of people with late-MDD (Hüls et al, 2020), found altered DNAm in the YOD1 locus, which is dysregulated in depression (Howren, Lamkin, & Suls, 2009) and its implicated in the regulation of inflammatory processes (Schimmack et al, 2017).…”
Section: Evidence Of Epigenetic Processes In Major Transdiagnostic Pa...mentioning
confidence: 99%
“…We further assessed over-representation for differentially expressed genes (DEGs) and genes proximal to differentially methylated CpG islands (DMGs) in the dorsolateral prefrontal cortex of patients with SCZ 21,22 and patients with MDD 7,23,24 and for loss of function intolerant genes (LoF) 25 .…”
Section: Biological and Functional Enrichment Analysis Of Sda Componentsmentioning
confidence: 99%